In vitro propagation and organ culture of Kacip Fatimah (Labisia pumila var. alata) - Jaafar, Nita Azlin (2013)
An in vitro propagation of Labisia pumila (L. pumila) var. alata was established using stem explants cultured on MS medium with the presence of different types of cytokinin and auxin. Three healthy shoots with fully expanded leaves per stem were obtained from stem explants culture on MS medium supplemented with 2.2 – 4.4 μM BAP. Addition of higher concentrations of BAP increased the multiple shoots formation however the leaves formed were very small. The shoots were elongated (up to 5 to 7 cm) in medium containing GA3 with a concentration ranging from 2.9 – 4.9 μM GA3. The elongated shoots were rooted using MS supplemented with different level of auxin. The highest number of roots were observed in medium containing 2 μM IBA (i.e average of 20 root segment per plantlet). Leaf explants cultured onto MS supplemented with NAA promoted the formation of short and thick root, while addition of IBA promoted the formation of long and thin roots. The highest number of root formation was seen in MS medium supplemented with 5μM NAA (i.e 13 root per explants). Following adventitious root induction, root suspension culture was successfully initiated using MS medium supplemented with 5μM NAA and 5 μM IBA. The highest fresh weight increment of the root culture was observed in MS medium supplemented with 5μM NAA (1g of root per month). In this study, attempts were made to induce hairy root from L. pumila var. alata using different strains of A. rhizogenes and different methods of infection. However, formation of hairy root was not observed even after 14 months of culture although the same set of A. rhizogenes were able to induce hairy root from leaf explants of tobacco. Thus, to understand the mechanism underlying the host-microbe interaction during infection process, a set of virulence (vir) genes in A. rhizogenes which are responsible for the interaction, transfer and integration of the T-DNA were analyzed. The vir genes expression in A. rhizogenes was compared in order to study the activity in the susceptible and recalcitrant plant. The expression of virA gene was observed to increase over time indicating successful interaction between plant host and A. rhizogenes. VirD2 gene was also observed to be expressed following infection thus it was hypothesized that the T-DNA was processed for further transportation into the plant host genome. The expression of genes responsible for transport channel, virB5 and virD4 was also observed thus indicating that the transfer of the T-DNA into the host plant may already take place. However, further analysis on the plant host genome shows that the T-DNA was not present after two days of infection indicating the possible loss of T-DNA.